2010
DOI: 10.1017/s0029665110001795
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, immunity and infection

Abstract: During the last few decades, scientific evidence has confirmed a wide range of health benefits related to regular physical activity. How physical activity affects the immune function and infection risk is, however, still under debate. Commonly, intensive exercise suppresses the activity and levels of several immune cells, while other immune functions may be stimulated by moderate physical activity. With this knowledge, the understanding of the relationship between different levels of physical activity on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 149 publications
(198 reference statements)
0
71
0
7
Order By: Relevance
“…High-volume and high-intensity pool-based training generally characterize precompetition periods. Clinical trials or properly conducted randomized trials are difficult to conduct with elite athletes, including swimmers, and therefore research on dietary practices and nutritional supplements is somewhat inconclusive (Romeo et al, 2010).…”
Section: Review Of Scientific Evidence For Nutrientsmentioning
confidence: 99%
“…High-volume and high-intensity pool-based training generally characterize precompetition periods. Clinical trials or properly conducted randomized trials are difficult to conduct with elite athletes, including swimmers, and therefore research on dietary practices and nutritional supplements is somewhat inconclusive (Romeo et al, 2010).…”
Section: Review Of Scientific Evidence For Nutrientsmentioning
confidence: 99%
“…[178][179][180] However, evidence for the effects of these nutritional supplementation strategies in impacting on immunosenescence is equivocal. 181 The inconsistent effects in the literature with micronutrient supplementation are most likely due to variance in dosage between studies and/or the initial nutritional status of individuals. 177 Although some studies have shown single and/or multivitamin or mineral supplementation can reverse age related declines in immune parameters, the risks associated with over-supplementation must be recognized whereby an approach to "right dose" rather than "megadose" is required.…”
Section: Nutritional Interventions In Ageing and Immunosenescencementioning
confidence: 99%
“…GMC-SF) but also an increase of antiinflammatory cytokines (IL-6, IL-10, IL-1ra), and an increase in concentration of an inflammatory protein (CRP). 4,15 Equine phagocytes sampled during exercise have an increased phagocytic capacity. 2,16 Many changes also occur during the period after exercise.…”
Section: Effect Of Exercisementioning
confidence: 99%
“…During the Open Window Period, the observed changes are namely: 15 • a reduction in the phagocytic capacity and oxidative burst of the neutrophils • a loss of the capacity of the macrophages to present the antigens to the lymphocytes (under-expression of the MHCII)…”
Section: Effect Of Exercisementioning
confidence: 99%